NEED ANALYSIS IN ENGLISH LANGUAGE LEARNING (ELL) CURRICULUM DEVELOPMENTS - Aprianto, Dedi (IKIP Mataram, 2016)
Lately, the arguable consensus of curriculum has many of cavities, the experts, academicians, and stake-holders, take position, in purpose of settling the curriculum problems. The globalizing aspects of life must have had the curriculum makers do the revisions as well as developments toward the present curriculum. Developing curriculum should be setting out needs of students hence it must be related to the contexts. So, competitiveness as the keystone to develop the students? needs. The development of the language learning curriculum should be paid attention in terms of constructed curriculum design having based on the theoretically-constituted frameworks. In the context of curriculum development, the basic assumption which should be considered in the educational programs, that is, the analysis of students? needs. Need analysis as part of system approach to curriculum developments in the scope of educational programs. This procedure let most of linguists to employ needs analysis as the basis to language learning curriculum. The usage of such procedure is underlain upon the learners? needs toward competitive world. In addition, the development and implementation of English Language Learning programs must be approached to the three aspects of English learning programs. These have different implications to the curriculum development, that is, each of them differs in relation to the input, process, and output. Thus, the general part of English language program curriculum design can be divided to forward design; concerning to the syllabus design, center design; the methodology of learning , and backward design; the assessment is based on the learners? outcomes. In turn, the three designs of language learning program must be in accordance with philosophical purposes of curriculum.